Structure-rheology relationship in polysulfones with triphenylphosphonium pendant groups systems for engineering applications - Filimon Anca (Proceedings of the International Symposium on Analytical and Environmental Problems, 2018)
Ionic polysulfones have received widespread attention for their promising roles in order to create new materials that can modulate the membrane properties. In this context, understanding of mechanisms developed in quaternized polysulfones with triphenylphosphonium pendant groups solutions, considering their specific interactions and the way in which these interactions affect their physical properties were evaluated by rheological investigations. Rheological behavior of this system, described by the non-linear flow curve, indicates the effect of the chemical structure of quaternized polysulfone, in order to facilitate the subsequently preparation of the active membranes. Thus, this study analyzes the processing-property relationship of solutions based on quaternized polysulfones and possibility of using it’s, with expected future developments in the engineering fields.